SOCIALIZATION OF STRATEGIES AND TIPS FOR SUCCESS IN TOEFL READING COMPREHENSION FOR 12TH GRADE STUDENTS AT SMK NEGERI 1 JORLANG HATARAN - Herman, Herman; Sinaga, Yanti Kristina; Sianturi, Melisa Angelia; Manalu, Bintoro Duma Erwanda B.; Sihotang, Elina Rosa; Sebayang, Santa Nananda (LPPM Univ. Ibn Khaldun Bogor, 2025)
This community service activity aimed to enhance the reading comprehension skills of 12th-grade students at SMK Negeri 1 Jorlang Hataran by introducing effective strategies and tips for success in the TOEFL Reading section. Recognizing that many students struggle with reading comprehension due to limited exposure to academic English and test-oriented strategies, this program provided targeted training focused on active reading techniques, vocabulary building, and identifying main ideas and supporting details. The activity was conducted through interactive workshops that included reading practice, discussions, and explanatory sessions. A qualitative approach was used to gather data, including observations, comprehension tests, and student questionnaires. Results indicate that students showed increased understanding of TOEFL question types, improved ability to identify key information in texts, and greater confidence in managing time during reading tasks. The feedback also reflected a positive change in student attitudes toward English reading, emphasizing the importance of early preparation and exposure to standardized testing formats. This initiative demonstrates that strategic socialization of reading techniques can significantly impact students' comprehension and test readiness. It also highlights the importance of equipping students with not only language proficiency but also the test-taking skills necessary for academic advancement. Future programs are encouraged to expand this approach to other sections of the TOEFL and provide continuous support for students’ English development.